2011
DOI: 10.1242/dev.065003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MAP3K1 enhances proliferation and apoptosis during retinal development

Abstract: SUMMARYPrecise coordination of progenitor cell proliferation and differentiation is essential for proper organ morphogenesis and function during mammalian development. The mitogen-activated protein kinase kinase kinase 1 (MAP3K1) has a well-established role in anterior eyelid development, as Map3k1-knockout mice have defective embryonic eyelid closure and an 'eye-open at birth' (EOB) phenotype. Here, we show that MAP3K1 is highly expressed in the posterior of the developing eye and is required for retina devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Acridine orange experiments revealed apoptotic cells in all explants, including controls, which should not be surprising as apoptosis is a naturally occurring process in the developing postnatal mouse retina (Williams et al 1990;Mongan et al 2011). None of the inhibitors increased the number of dying cells, indicating that the phenotypes observed after compound administration, that is, a reduced axonal outgrowth, were not because of a general toxic effect of the MMP-inhibiting compounds.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Acridine orange experiments revealed apoptotic cells in all explants, including controls, which should not be surprising as apoptosis is a naturally occurring process in the developing postnatal mouse retina (Williams et al 1990;Mongan et al 2011). None of the inhibitors increased the number of dying cells, indicating that the phenotypes observed after compound administration, that is, a reduced axonal outgrowth, were not because of a general toxic effect of the MMP-inhibiting compounds.…”
Section: Discussionmentioning
confidence: 71%
“…; Mongan et al . ). None of the inhibitors increased the number of dying cells, indicating that the phenotypes observed after compound administration, that is, a reduced axonal outgrowth, were not because of a general toxic effect of the MMP‐inhibiting compounds.…”
Section: Discussionmentioning
confidence: 97%
“…Morphology was analyzed at P7 by H&E staining. For the artificial EOB model, the surgical procedure was designed according to a previous study (40). Neonatal spns2 +/+ rats were cryoanesthetized, and eyelid was carefully separated.…”
Section: Quantification Of Retinal Cellsmentioning
confidence: 99%
“…A previous study showed that impaired cell proliferation was associated with eyelid closure (Mongan et al, 2011). Other studies also reported that apoptosis affects this process.…”
Section: Gene Namementioning
confidence: 93%